Assimilation of Tung Chung Shu’s Philosophy and the Development of Multiculturalism - Lasiyo, Lasiyo (Jurnal Filsafat "WISDOM", 2024)
The purpose of this article is to explore the thoughts of the philosopher Tung Chung Shu who is a figure in Chinese philosophy. Tung Chung Shu managed to compile several aspects of philosophy and culture that developed in China during the Han dynasty. Tung Chung Shu's thought has relevance to the development of multiculturalism, especially in Indonesia amid globalization today. The condition of the Chinese nation has a different cultural background and has succeeded in reformulating the unifying ideology of the country so that it can improve the condition of a society that is experiencing chaos. The philosophy and culture of the Chinese nation that developed when in this condition was the Han Dynasty which was dominated by Taoism, Legalism, and Confucianism. A Chinese philosopher, Tung Chung Shu, combined the three schools with the core teachings of jen, yi, l, chi, and hsin with the main goal of realizing a happy, prosperous, and safe society. The situation of differences that exist in people's lives gave birth to multiculturalism which offers a cultural paradigm to understand and interpret the differences that develop in people's lives. This research uses the abstraction analysis method and then analyzes it through a comparative interpretative approach that begins with description and historical continuity. The results showed that (1) the condition of differences in society can be avoided from conflict if the government can implement multiculturalism policies in regulating the order of government as in Tung Chung Shu's thinking about good governance (2) the condition of a country depends on the attitude of the country's leaders so that the condition of multicultural society can be safe, harmonious, peaceful, prosperous cannot be separated from the role of state leaders (3) in addressing differences need the attitude of wisdom, humanity, courage, wisdom and virtue as the philosophical thought of Tung Chung Shu. In line with the conditions of the multicultural Indonesian nation, Tung Chung Shu's thoughts can be a reference in efforts to develop multiculturalism in Indonesia. This argument is supported by the situation and conditions of the Indonesian nation which has a diversity of ethnicities, cultures, religions, regions, and different cultural traditions.